2006
DOI: 10.2527/jas.2005-606
|View full text |Cite
|
Sign up to set email alerts
|

Socializing piglets before weaning: Effects on behavior of lactating sows, pre- and postweaning behavior, and performance of piglets

Abstract: This study evaluated how socializing piglets before weaning affects behavior of lactating sows and the pre- and postweaning behavior and performance of piglets. Two farrowing rooms, each with 6 pens, and 1 nursery with 4 pens were used. In total, data were obtained from 24 sows and their litters. In each farrowing room, the solid barriers between 3 farrowing pens were removed on d 12 after farrowing, and the sows remained confined in their crates (experimental group). In the other 3 farrowing pens of each farr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 16 publications
5
67
0
Order By: Relevance
“…socialised) kept in intact groups than among unknown mixed pigs. This is in accordance with Kutzer et al (2009) andHessel et al (2006) who compared aggressive behaviour between socialised and control piglets for 48 h after mixing at weaning. According to D'Eath (2005), socialised piglets learn social skills that enable them to rapidly form stable hierarchies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…socialised) kept in intact groups than among unknown mixed pigs. This is in accordance with Kutzer et al (2009) andHessel et al (2006) who compared aggressive behaviour between socialised and control piglets for 48 h after mixing at weaning. According to D'Eath (2005), socialised piglets learn social skills that enable them to rapidly form stable hierarchies.…”
Section: Discussionsupporting
confidence: 91%
“…Socialising piglets has been performed in several studies (D'Eath, 2005;Hessel et al, 2006;Kutzer et al, 2009;Fà brega et al, 2013), but it has not become a common practice in conventional production. The fact that entire males perform more aggressive and sexual behaviour than castrates, in combination with the ambition to stop castration, increases the relevance of early socialising in conventional pig production.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the foraging activities displayed outside the nest site satisfy the piglets' desire to perform exploratory behaviours, rooting and manipulating substrates and beginning the adaptation to solid food intake. The early socialisation benefits the piglets by reducing the impact of weaning (Pajor et al, 1999;Hessel et al, 2006), particularly reducing the effects of mixing aggression. D'Eath (2005) demonstrated that pre-weaning mixing of piglets reduced aggression levels at weaning and this socialisation appeared to equip piglets with social skills that benefitted them in the long term, enabling them to more rapidly form stable dominance hierarchies during future aggressive encounters with unfamiliar pigs.…”
Section: Nest Departure and Social Integrationmentioning
confidence: 99%
“…(Melotti et al, 2011). Compared with piglets that were first mixed at weaning at an age of 3 to 4 weeks, piglets that could interact with one or more litters before weaning showed less aggression (Weary et al, 2002;Hessel et al, 2006;Kutzer et al, 2009) and skin lesions (Parratt et al, 2006) after weaning when kept with familiar piglets. This was likely because new hierarchies did not need to be established.…”
Section: Piglet (Social) Developmentmentioning
confidence: 99%
“…Potential factors contributing to a better adaptation to the post-weaning situation are improved social skills, the absence of mixing of piglets at weaning, increased experience with solid feed or a higher weaning age (Berkeveld et al, 2009). For instance, piglets mingled with other litters during lactation gained 0.8 to 1.0 kg more in the 5 weeks post-weaning compared with housing without contact possibilities (Hessel et al, 2006;Kutzer et al, 2009).…”
Section: Piglet (Social) Developmentmentioning
confidence: 99%